PERFORMANCE OF A SOLAR INTEGRATED HEAT PUMP AIR-CONDITIONER, WATER HEATER AND DRYER - Hawlader, Mohammad Nurul Alam; Ye, Shaochun (Ambient Press Ltd, 2008)
In this study, a solar assisted heat-pump system for air-conditioning, water heating and drying was designed, constructed and performance evaluated. The three applications can be served simultaneously or independently. The presence of an innovative two-phase unglazed solar evaporator-collector, where refrigerant R-134a was used as the fluid, enabled the system to operate round the clock. The evaporator-collector gained, instead of losing, significant amount energy from the ambient due to low operating temperature of the collector. A large fraction of the energy requirements is met by a combination of energy collected from sun, ambient and the energy recovered from a vapour compression heat-pump system, which also serves as an air-conditioner. One of the two condensers served as a water heater and the other for heating the air to the required temperature for drying purposes. A series of experiment were conducted under the meteorological conditions of Singapore to evaluate the system performance under different applications and operating conditions. Maximum COP achieved during the experiment was about 6.8. This system could ensure a long-term operation under different working conditions and reduce a lot of building thermal cost, especially for hotel and hospital in the tropics.